A Teacher Talks - Marielsa López (Universidad Autónoma de Madrid, 2018)
The following article shows how a school can overcome a large variety of problems using standard resources for a Latin-American school. The exact method followed by this school cannot be used as a recipe that can be used by other schools to attain success; even in the same country or region. This school serves as an inspiration, showing that by embracing its own characteristics; and adopting creative solutions almost anything is achievable.  It is also shown that even though this school has the most severe problems, it also obtained the best results. Thus, what is exposed here shows not the optimal results; but the best results attainable by the condition of the school. It is possible for a school to become an instrument of social progress (and perhaps a way to climb out of poverty); if it so chooses to be.